The Associations of Platelet Activation and Coagulation Parameters with Obstructive Sleep Apnoea: A Large-Scale Observational Study - Jundong Yang; Wenjun Xue; Zhicheng Wei; Caiqiong Hou; Huaming Zhu; Huajun Xu; Xiaolin Wu; Yunhai Feng; Xinyi Li (International Journal of Clinical Practice, 2023)
Objectives. Obstructive sleep apnoea (OSA) is associated with an increased risk of cardiovascular disease, with alterations in coagulability suspected as the mediating factor. This study explored blood coagulability and breathing-related parameters during sleep in patients with OSA. Design. Cross-sectional observational study. Setting. Shanghai Sixth People’s Hospital. Participants. 903 patients diagnosed by standard polysomnography. Main Outcome and Measures. The relationships between coagulation markers and OSA were evaluated using Pearson’s correlation, binary logistic regression, and restricted cubic spline (RCS) analyses. Results. The platelet distribution width (PDW) and activated partial thromboplastin time (APTT) decreased significantly with increasing OSA severity (both p<0.001). PDW was positively associated with the apnoea-hypopnea index (AHI), oxygen desaturation index (ODI), and microarousal index (MAI) (ß = 0.136, p<0.001; ß = 0.155, p<0.001; and ß = 0.091, p=0.008, respectively). APTT was negatively correlated with AHI (ß = −0.128, p<0.001) and ODI (ß = −0.123, p=0.001). PDW was negatively correlated with percentage of sleep time with oxygen saturation below 90%(CT90) (ß = −0.092, p=0.009). The minimum arterial oxygen saturation (SaO2) correlated with PDW (ß = −0.098, p=0.004), APTT (ß = 0.088, p=0.013), and prothrombin time (PT) (ß = 0.106, p=0.0003). ODI was risk factors for PDW abnormalities (odds ratio (OR) = 1.009, p=0.009) after model adjustment. In the RCS, a nonlinear dose-effect relationship was demonstrated between OSA and the risk of PDW and APTT abnormalities. Conclusion. Our study revealed nonlinear relationships between PDW and APTT, and AHI and ODI, in OSA, with AHI and ODI increasing the risk of an abnormal PDW and thus also the cardiovascular risk. This trial is registered with ChiCTR1900025714.